Expression of Angiotensin II Receptor-1 in Human Articular Chondrocytes. (30th December 2012) - Kawakami, Yuki; Matsuo, Kosuke; Murata, Minako; Yudoh, Kazuo; Nakamura, Hiroshi; Shimizu, Hiroyuki; Beppu, Moroe; Inaba, Yutaka; Saito, Tomoyuki; Kato, Tomohiro; Masuko, Kayo
Abstract : Background . Besides its involvement in the cardiovascular system, the renin-angiotensin-aldosterone (RAS) system has also been suggested to play an important role in inflammation. To explore the role of this system in cartilage damage in arthritis, we investigated the expression of angiotensin II receptors in chondrocytes. Methods . Articular cartilage was obtained from patients with osteoarthritis, rheumatoid arthritis, and traumatic fractures who were undergoing arthroplasty. Chondrocytes were isolated and cultured in vitro with or without interleukin (IL-1). The expression of angiotensin II receptor types 1 (AT1R) and 2 (AT2R) mRNA by the chondrocytes was analyzed using reverse transcription-polymerase chain reaction (RT-PCR). AT1R expression in cartilage tissue was analyzed using immunohistochemistry. The effect of IL-1 on AT1R/AT2R expression in the chondrocytes was analyzed by quantitative PCR and flow cytometry. Results . Chondrocytes from all patient types expressed AT1R/AT2R mRNA, though considerable variation was found between samples. Immunohistochemical analysis confirmed AT1R expression at the protein level. Stimulation with IL-1 enhanced the expression of AT1R/AT2R mRNA in OA and RA chondrocytes. Conclusions . Human articular chondrocytes, at least partially, express angiotensin II receptors, and IL-1 stimulation induced AT1R/AT2R mRNA expression significantly.